2012
DOI: 10.4103/2224-3151.206917
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of childhood tuberculosis: a case control study from rural Bangladesh

Abstract: Age, education, father's occupation, crowding, kitchen location and intimate contact with a TB case were significantly associated with smear-positive childhood TB.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
1
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 1 publication
2
15
1
3
Order By: Relevance
“…In contrast to this, Gupta R et al, found in his study on children, indicating the high prevalence of childhood tuberculosis in the younger age group. 7,8 Similar findings were reported in hospital-based study done by Sharma S et al, on extra-pulmonary TB during January 1995 -July 2004 at LRS Institute of Tuberculosis and Respiratory Diseases, New Delhi. Patient's where, majority were females (61%) and males were 39%.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…In contrast to this, Gupta R et al, found in his study on children, indicating the high prevalence of childhood tuberculosis in the younger age group. 7,8 Similar findings were reported in hospital-based study done by Sharma S et al, on extra-pulmonary TB during January 1995 -July 2004 at LRS Institute of Tuberculosis and Respiratory Diseases, New Delhi. Patient's where, majority were females (61%) and males were 39%.…”
Section: Discussionsupporting
confidence: 79%
“…Karim MR et al, showed association of maternal education with prevalence of TB cases was statistically significant (p=0.002) in their study. 7 Similarly, Joshi S et al, showed that fathers of 24.24% paediatric patients were illiterate, 13.93% were from middle school, 13.33% from primary school, 32.12% high school. 12 10.30% were intermediate, 4.24% were graduate and the fathers with highest level of education i.e.…”
Section: Discussionmentioning
confidence: 94%
“…4 7 Anak dengan hunian yang padat berisiko lima kali terinfeksi TB. 8 Infeksi TB sering terjadi pada masa kanak-kanak dan anak dengan infeksi TB berisiko tinggi sakit TB, yang paling rentan anak usia <5 tahun. 3 Dalam penelitian ini didapatkan anak usia <5 tahun memiliki persentase yang lebih tinggi dibandingkan usia >5 tahun, meskipun perbedaan antara kasus dan kontrol tidak bermakna.…”
unclassified
“…Chest X-rays of the index cases may be used to assess the severity and location of abnormalities in the lungs. 15 Extensive infiltrates and cavities in the upper lobe were risk factors in the transmission of tuberculosis from adults to children. 12 Adverse environmental conditions such as poor ventilation, humid housing conditions, and the number of occupants in the home may also increase tuberculosis incidence.…”
Section: Discussionmentioning
confidence: 99%